2004
DOI: 10.1161/01.atv.0000104028.07929.72
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Supplementation in Patients With Carotid Atherosclerosis

Abstract: Objective-Oxidative stress is believed to play a pivotal role in the initiation and progression of atherosclerosis. We analyzed whether vitamin E supplementation influences oxidative stress in plasma and atherosclerotic plaques of patients with severe atherosclerosis. Methods and Results-In 16 patients who were candidates for carotid endarterectomy and in 32 age-and sex-matched controls, plasma levels of 7␤-hydroxycholesterol, 7-ketocholesterol, cholesterol, and vitamin E were measured. Patients were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…If this finding will be confirmed in larger series, the association of high plasma 7␤-hydroxycholesterol and IPGF could be explained by the oxysterol biological activities rather than merely reflect more advanced liver disease and could support attempts to reduce plasma oxysterol concentration with antioxidant supplementation in patients undergoing OLT. 26 In keeping with this hypothesis, plasma oxysterols might be potentially toxic at physiological concentrations, in analogy to their injurious effect on arterial endothelium in atherosclerosis, on sinusoidal endothelial cells whose damage is a key step in the hepatic ischemia-reperfusion injury. 1,4,28,[38][39][40] In the present study, we tried to indirectly identify the site of enhanced free radical flux in cirrhosis in vivo by comparing the oxidative stress/antioxidant status at the plasma and the hepatic tissue level in cirrhosis, at tissue level in the liver with cirrhosis and the normal liver, and at the plasma level in patients with cirrhosis before and 1 month after OLT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If this finding will be confirmed in larger series, the association of high plasma 7␤-hydroxycholesterol and IPGF could be explained by the oxysterol biological activities rather than merely reflect more advanced liver disease and could support attempts to reduce plasma oxysterol concentration with antioxidant supplementation in patients undergoing OLT. 26 In keeping with this hypothesis, plasma oxysterols might be potentially toxic at physiological concentrations, in analogy to their injurious effect on arterial endothelium in atherosclerosis, on sinusoidal endothelial cells whose damage is a key step in the hepatic ischemia-reperfusion injury. 1,4,28,[38][39][40] In the present study, we tried to indirectly identify the site of enhanced free radical flux in cirrhosis in vivo by comparing the oxidative stress/antioxidant status at the plasma and the hepatic tissue level in cirrhosis, at tissue level in the liver with cirrhosis and the normal liver, and at the plasma level in patients with cirrhosis before and 1 month after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…26,32 MDA assays, albeit useful in in vitro systems, are unsatisfactory and give contrasting results when applied in vivo. In fact, increased blood levels of MDA were found in HCV chronic liver disease C by Yadav et al 21 but not by Jain et al, 16 who, however, found increased levels of urinary isoprostanes, the gold standard for the assessment of systemic oxidative injury in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 They suggest that our conclusion should not be based on the comparison of vitamin E/cholesterol ratios in plaque versus control plasma nor on the use of 7␤hydroxy-cholesterol/vitamin E ratios.…”
Section: In Responsementioning
confidence: 96%